2012
DOI: 10.4274/jcrpe.801
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Deficiency and Diabetes Insipidus as a Complication of Endoscopic Third Ventriculostomy

Abstract: Endoscopic third ventriculostomy (ETV) has become the procedure of choice for the treatment of obstructive hydrocephalus in children and adults. Endocrinological complications of ETV in children are rare. Diabetes insipidus (DI) is the most common and accounts for only 0.5% of complications from ETV. The majority of documented cases are transient. To date, there are no documented cases of multiple pituitary hormone deficiencies. We present here a 6-year-old girl with growth hormone deficiency and permanent DI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Diabetes insipidus was reported in 0.64% of cases, weight gain in 0.27%, and precocious puberty in 0.04% 6) . Additionally, amenorrhea and partial growth hormone deficiency were reported due to hypothalamic injury 17 , 26) .…”
Section: Complications Of Endoscopic Third Ventriculostomymentioning
confidence: 99%
“…Diabetes insipidus was reported in 0.64% of cases, weight gain in 0.27%, and precocious puberty in 0.04% 6) . Additionally, amenorrhea and partial growth hormone deficiency were reported due to hypothalamic injury 17 , 26) .…”
Section: Complications Of Endoscopic Third Ventriculostomymentioning
confidence: 99%
“…Several single-case studies have reported electrolyte or single-parameter endocrine abnormalities (diabetes insipidus and secondary amenorrhea) after ETV [3,35,36,37,38,39,40,41,42,43,44,45] (table 1). Goumnerova and Frim [3] reported 1 patient who developed a transient increase in thirst and appetite that resolved within 3 months after ETV complicated by intraoperative transient bradycardia; the endocrine evaluation was normal.…”
Section: Discussionmentioning
confidence: 99%
“…Although ETV is thought to be safe, various complications due to damage to neural and vascular structures have been reported [4,9,11,15,16,19,28,29,30,31,32,33]. Injury to the hypothalamic-pituitary axis, followed by clinically relevant endocrine sequelae, has been rarely described in the literature [4,28,34,35,36,37,38,39,40,41,42,43,44,45]. …”
Section: Case Reportmentioning
confidence: 99%
“…Pioglitazone function as insulin sensitizer and thus, enhance the insulin action and improve hyperglycemia in patients with T2DM [10]. TZDs have also been shown to decrease pancreatic β cell destruction and therefore have a potential role in the treatment and prevention of T1DM [11].…”
Section: Introductionmentioning
confidence: 99%